Edukasi Pemanfaatan Limbah Sisa Makanan Menjadi Produk Yang Bernilai Ekonomis - Teuku Athaillah; Bagio; Hasanuddin Husin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Poor waste management has become a problem in Kuta Jeumpa Village of Jeumpa Sub-district of Aceh Barat Daya Regency. The people of Kuta Jeumpa Village still throw their household wasteinto the river. As the result, the water of Putroe Aloh River in Kuta Jeumpa Village is filled with household waste. To overcome this situation, waste management education is needed to be carried out for the people of Kuta Jeumpa to manage their waste properly. The people of Kuta Jeumpa village need to be taught on how to turn waste into a source of income, for example by introducing on how to make processed food from household waste. After the the people of Kuta Jeumpa received the waste management education, they have succeeded in making new processed food products from household waste with the help of university students and lecturers. The products produced can provide profit value for the community. In addition, the community was also educated to no longer throw their household waste into the river.